2010
DOI: 10.1088/0004-637x/722/1/358
|View full text |Cite
|
Sign up to set email alerts
|

ASUZAKUX-RAY STUDY OF THE PARTICLE ACCELERATION PROCESSES IN THE RELATIVISTIC JET OF BLAZAR Mrk 421

Abstract: We report on the findings of a 364 ksec observation of the BL LAC object Mrk 421 with the X-ray observatory Suzaku. The analysis in this paper uses fluxes and hardness ratios in the broad energy range from 0.5 keV to 30 keV. During the course of the observation, the 0.5 keV -30 keV flux decreased by a factor of ∼2 and was accompanied by several large flares occurring on timescales of a few hours. We find that fitting a broken power model to spectra from isolated epochs during the observation describes the data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 57 publications
2
21
1
1
Order By: Relevance
“…They analyzed the spectrum with a parametric forward-fitting synchrotron model and with a particle acceleration model and discussed the possibilities in the context of diffusive acceleration of electrons. The third observation, ID 703043010, begun on 5 May 2008, was analyzed by Garson et al (2010) and they found that a broken power-law model fit the spectra very well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They analyzed the spectrum with a parametric forward-fitting synchrotron model and with a particle acceleration model and discussed the possibilities in the context of diffusive acceleration of electrons. The third observation, ID 703043010, begun on 5 May 2008, was analyzed by Garson et al (2010) and they found that a broken power-law model fit the spectra very well.…”
Section: Discussionmentioning
confidence: 99%
“…Suzaku consists of: the X-ray Imaging Spectrometer (XIS, Koyama et al 2007) for the 0.2−10 keV low energy band; the Hard X-ray Detector (HXD, Takahashi et al 2007;Kokubun et al 2007), which utilizes PIN silicon diodes and is sensitive over 12−60 keV; and the GSO scintillator, which extends the detection ability to hundreds of keV. Mrk 421 was observed three times by Suzaku on 2006 April 28 (ID 701024010), 2008 May 5 (ID 703043010) and 2008 December 3 (ID 703020010) (Ushio et al 2009(Ushio et al , 2010Garson et al 2010). The observations are listed in Table 1 in order of the ObsID and the total elapsed time.…”
Section: Suzaku Archival Data Reductionmentioning
confidence: 99%
“…These non-detections of time lags might be due to the fact that the actual time lag is likely intra-day, which is difficult to resolve using our light curves of several-day time resolution. In Garson et al (2010), two flares of Mrk 421 lasting for 0.5 days showed several-hour time lags between the 0.5-2 keV and 2-10 keV light curves, and displayed different movements in the hardness-flux plot. Krawczynski et al (2000) indicated that the time lag between 3 keV and 25 keV is smaller than 15 hours in Mrk 501.…”
Section: Electron Spectral Hysteresismentioning
confidence: 99%
“…Fig. 6 of Garson et al (2010) displays both clockwise and tilted figure-8 hysteresis in 0.5−2 keV Suzaku data spanning several hours for modest Mrk 421 activity over 4 days in May 2008, a period when the source did not exhibit strong flares. More recently, Figs.…”
Section: Case 1: Variation Of Injection Luminositymentioning
confidence: 99%